2022
DOI: 10.1186/s13024-021-00514-8
|View full text |Cite
|
Sign up to set email alerts
|

Murine roseolovirus does not accelerate amyloid-β pathology and human roseoloviruses are not over-represented in Alzheimer disease brains

Abstract: Background The role of viral infection in Alzheimer Disease (AD) pathogenesis is an area of great interest in recent years. Several studies have suggested an association between the human roseoloviruses, HHV-6 and HHV-7, and AD. Amyloid-β (Aβ) plaques are a hallmark neuropathological finding of AD and were recently proposed to have an antimicrobial function in response to infection. Identifying a causative and mechanistic role of human roseoloviruses in AD has been confounded by limitations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 82 publications
1
20
0
Order By: Relevance
“…Rizzo et al [ 16 ] found a correlation between KIR2DS2/KIR2DL2/C1, a lower MMSE score (representative for AD), and an increased susceptibility to HHV-6A infection. On the other hand, a very recent study on AD murine models (5XFAD mice) did not support the role of murine or human roseola viruses in the development of AD-specific Aβ senile plaque formation [ 26 ]. The authors do, however, demonstrate HHV-6 involvement in generating and maintaining neuroinflammation, but the fact that the pathological formation of Aβ agglomeration is not achieved is further evidence that there are other mechanisms—still incompletely elucidated—involved in this complex neurodegenerative process.…”
Section: Evidence Of Hhv-6 Infection and Alzheimer’s Diseasementioning
confidence: 99%
“…Rizzo et al [ 16 ] found a correlation between KIR2DS2/KIR2DL2/C1, a lower MMSE score (representative for AD), and an increased susceptibility to HHV-6A infection. On the other hand, a very recent study on AD murine models (5XFAD mice) did not support the role of murine or human roseola viruses in the development of AD-specific Aβ senile plaque formation [ 26 ]. The authors do, however, demonstrate HHV-6 involvement in generating and maintaining neuroinflammation, but the fact that the pathological formation of Aβ agglomeration is not achieved is further evidence that there are other mechanisms—still incompletely elucidated—involved in this complex neurodegenerative process.…”
Section: Evidence Of Hhv-6 Infection and Alzheimer’s Diseasementioning
confidence: 99%
“…Together with several recent studies [38, 62, 63], our work raises serious doubts as to whether a direct causal relationship between viral infections and Aβ pathology exists. Analysis of brain tissues from latently HSV‐1 infected patients and individuals with HSE did not reveal Aβ or hyperphosphorylated tau pathology [62].…”
Section: Discussionmentioning
confidence: 65%
“…Similarly, in hAβ mice with acute HSE, the levels of APP/Aβ in individual neurons did not change upon HSV‐1‐infection. In another recent study, a series of experiments examined 5XFAD mice infected with murine roseolovirus (MRV) via two different routes (peripheral/intracranial) at various time points (before/after spontaneous formation of Aβ plaques); the mice were analyzed at multiple time‐points post infection (acute/chronic) [ 63 ]. In young 5XFADs, MRV infection did not induce the formation of Aβ plaques de novo [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, administration of nonlethal viral dose to these mice led to Aβ deposits surrounding the viruses [ 161 ]. These observations were questioned by some subsequent studies [ 172 , 173 ]. However, this discrepancy could be explained by viral particle doses or viral strains/species used, which may differ in their sensitivity to Aβ.…”
Section: Protective Role Of Amyloid Betamentioning
confidence: 98%